(untitled) (Italian Journal of Public Health, 2009)
Background: The impact of universal vaccination programmes in terms of reduction of disease burden is not questioned very much in the scientific community. Nevertheless assessing safety and efficacy of vaccination products in the field is an essential part of the success of any vaccination programme. In addition to that, there are several aspects of vaccination programmes that have to be evaluated and carefully assessed in order to improve the overall quality of vaccination programmes. Methods: Several different epidemiological methods have been developed during the last decades for these purposes. A critical review of innovative epidemiological methods used for assessing vaccines in the field was undertaken. Results: Availability of innovative methods and progress made in the field of health informatics allow easy evaluation of large volumes of information. Conclusions: In addition to scientific and technical support, political commitment is required in order to increase the amount of resources available for public health professionals. International organisations can play an important role at the EU level.